Implementation of the Sustainable Development Goals Program in Oabikase Village, West Insana District, North Central Timor Regency - Naisoko, Liberius (Jurnal Ilmu Administrasi Negara (JUAN), 2024)
Implementation of the Sustainable Development Goals (SDGs) Program in Oabikase Village, West Insana District, North Central Timor Regency. Problem Formulation "How is the implementation of the sustainable development goals (SDGs) program? The aim of this research is to describe and analyze the implementation of the Sustainable Development Goals (SDGs) program. The research method is qualitative with descriptive data analysis techniques, data collection techniques through interviews and documentation. The research results show that the implementation of the sustainable development goals (SDGs) program was carried out well, but there were several deficiencies such as human resources which resulted in less efficient allocation of funds so that people did not feel the benefits of the SDGs and there was a lack of health and sanitation facilities and health services. With the implementation of development in the fields of Poverty, Health and Sanitation, with the first research sub-focus, implementation elements are certain factors for implementing policies, programs or projects effectively. This includes planning, implementation, monitoring and evaluation. Secondly, the existence of a program being implemented is the implementation of a plan or series of actions designed to achieve the objectives of a program. Third, the target group is a group of individuals who are the focus of a particular program, policy or initiative. In society, diversity of characters will influence the implementation of development starting from choosing and selecting methods or techniques for implementing programs. This is proven by changes in the village. with programs in the fields of poverty, health and sanitation. However, there are obstacles in implementation, namely a lack of human resources which results in less effective and efficient fund management